Perceived risk towards continual usage intention of online banking - Mohd Tahir, Hirnissa; Mohd Ashhari, Zariyawati; Tye, Ying Ying (Academia Industry Networks, 2019)
This study aims to determine the perceived risk towards continual usage intention of online banking in Malaysia. The perceived risk variables are adopted from Theory of Perceived Risk to further examine the influence to continual usage intention of online banking in Malaysia which included privacy risk, financial risk, social risk, time risk, performance risk and psychological risk. This research was distributed through online questionnaire by using convenient sampling technique to collect the data. A total of 400 respondents were obtained from online banking user who are above 18 years old in Malaysia. Multiple Linear Regression analysis was used to analyze the relationship between perceived risk and continual usage intention of online banking in Malaysia. The result revealed two perceived risks (time risk and psychological risk) were found to significantly influence the continual usage intention of online banking in Malaysia.